Systemic cytokines drive conserved severity-associated myeloid responses across bacterial and viral infections - Kimberly Kajihara; Donghong Yan; Gretchen L. Seim; Hannah Little-Hooy; Jing Kang; Cynthia Chen; Marco De Simone; Tim Delemarre; Spyros Darmanis; Haridha Shivram; Rebecca N. Bauer; Carrie M. Rosenberger; et al. (Communications Biology)
Abstract Both bacterial and viral infections can trigger an overwhelming host response, leading to immunopathology and organ dysfunction. Multiple studies have reported dysregulated myeloid cell states in patients with bacterial sepsis or severe SARS-CoV-2 infection. However, their relevance to viral infections other than COVID-19, the factors driving their induction, and their role in tissue injury remain poorly understood. Here, we performed a multi-cohort analysis of single cell and bulk transcriptomic data from 1845 patients across 25 studies. Our meta-analysis revealed a conserved severity-associated gene signature pointing to emergency myelopoiesis (EM) and increased IL1R2 expression in monocytes and neutrophils from patients with bacterial sepsis, COVID-19, and influenza. Analysis of tocilizumab-treated COVID-19 patients showed that IL-6 signaling blockade partially reduces this signature and results in a compensatory increase in G-CSF. To validate the role of these cytokines in vivo, we used a mouse model of influenza infection that recapitulates severity-associated increases in IL1R2+ monocytes and IL1R2hi neutrophils, and demonstrate that combined IL-6 and G-CSF blockade inhibits their production. Our study demonstrates the cooperative role of G-CSF and IL-6 in driving the production of severity-associated IL1R2+ myeloid cells and highlights the link between myeloid dysregulation and tissue injury during severe infection.